The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11431-011-4371-7
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of water release operations on algal blooms in a tributary bay of Three Gorges Reservoir

Abstract: Water release operation is crucial for water quality in large reservoirs such as Three Gorges Reservoir (TGR), because it determines the hydrodynamics and hence the self-purification capability. As algal blooms were often observed in some tributary bays of TGR during the release periods, high frequency field observations were carried out in a typical eutrophic tributary bay (Xiangxi River) from February 9 to May 10, 2009. In this paper we assess the hydrodynamic behaviour, density stratification, and trophic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…River reservoirs, being both a river and a reservoir, are commonly used for water supply, flood control, irrigation as well as hydroelectric power generation [10,11]. These dammed rivers are generally characterized by great lengths, slow water flow velocity and thus long hydraulic residence time [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…River reservoirs, being both a river and a reservoir, are commonly used for water supply, flood control, irrigation as well as hydroelectric power generation [10,11]. These dammed rivers are generally characterized by great lengths, slow water flow velocity and thus long hydraulic residence time [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Jiang [19] verifies the result and emphasizes that thermal stratified flow by water temperature difference should be considered for the algal bloom control. Then, analysis is conducted to validate that a wave-type water release operation is beneficial in reducing algal bloom in the tributary [20]. Furthermore, a feasible water level process of TGR is also demonstrated to be helpful for controlling phytoplankton blooms in the tributary bays by the analysis of mixing depth [21].…”
Section: Introductionmentioning
confidence: 99%
“…Since the discharge and pollutant load into XR are predominantly larger [11], other tributaries were considered as closed bay in the simulation. Serious water quality problems had occurred in these tributaries due to insufficient water mixing or flowing based on the in-situ observation [4]. Therefore, a high initial concentration of nutrients and chlorophyll-a is used in the calculation.…”
Section: Study Casementioning
confidence: 99%
“…Particularly, many hydrodynamic and water quality models have been applied for examining the TGR algal blooms, which include 1-Dimensional [1], vertical 2-Dimensional [2] and 3-Dimensional [3] models. From the previous works, it was found that the flowing field, solute transport and phytoplankton biomass evolution in TGR present significant spatial and temporal variations [4]; hence, a 3-dimensional model is considered better suited for the modeling purpose. Generally, the 3-dimensioal models can be divided into structured and unstructured meshes [3]; however, the model cannot well follow the complex boundary and subaqueous relief in TGR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation